2021
DOI: 10.53908/nmmr.290304
|View full text |Cite
|
Sign up to set email alerts
|

Does Work-Life Balance Mediate the Relationship of Perceived Organizational Support and Job Satisfaction for Healthcare Workers? A Study on Female Nurses in India

Abstract: Purpose: Studies time and again ascribe increased attrition in the nursing profession to poor organizational support and issues of work-life balance resulting in higher levels of job dissatisfaction among nurses. Considering this background, we conceptualized a model (POS-WLB-JS) anchored on organizational support theory and examined the mediating influence of work- life balance in the relationship of perceived organizational support and job satisfaction for female nurses in the Indian healthcare ecosystem. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…This result correspondent with Sheikh (21) study who indicated that a positive influence of perceived organizational support on work-life balance. Also, Dubey and Riasudeen (22) studied the mediating influence of work-life balance in the relationship between perceived organizational support and job satisfaction for female nurses in the Indian healthcare ecosystem and found that Perceived organizational support and work-life balance have a significant and positive relationship between them.…”
Section: Concerningmentioning
confidence: 99%
“…This result correspondent with Sheikh (21) study who indicated that a positive influence of perceived organizational support on work-life balance. Also, Dubey and Riasudeen (22) studied the mediating influence of work-life balance in the relationship between perceived organizational support and job satisfaction for female nurses in the Indian healthcare ecosystem and found that Perceived organizational support and work-life balance have a significant and positive relationship between them.…”
Section: Concerningmentioning
confidence: 99%